THERMODYNAMIC RESEARCH ON THE INHIBITORS OF CORONAVIRUS THROUGH DRUG DELIVERY METHOD - Fatemeh Mollaamin (Journal of the Chilean Chemical Society, 2021)
Based on CoVs, the genomic structure is arranged in a +ssRNA with   approximately 30 kb in length  which is the biggest known RNA viruses  including  a 5′-cap structure and 3′-poly-A tail.  CoVs, (positive stranded RNA viruses), can infect humans and multiple species of animals, cause enteric, respiratory, and central nervous system diseases in many species. These viruses are important for anti-CoV drug delivery through a pivotal function in viral gene expression and replication through the proteolytic processing of replicase polyproteins.In this paper, it has been illustrated  the linkage  of 6 inhibitors of N-[[4-(4-methylpiperazin-1-yl)phenyl]methyl]-1,2-oxazole-5-carboxamide, “inh1”, NSC 158362, “inh2”,JMF 1586 ,“inh3”,(N-(2-aminoethyl)-1-1ziridine-ethanamine) , “inh4” ,[(Z)-1-thiophen-2-ylethylideneamino]thiourea, “inh5” and Vanillinbananin, “inh6”,  to CoVs by forming the complexes of  “inhibitor- CoV” in water phase  through   the H-bonding using  some physico-chemical properties including  heat of formation , Gibbs free energy , electronic energy , charge distribution of active parts in the  hydrogen bonding ,NMR estimation of inhibitor jointed to the database amino acids fragment of  Tyr-Met-His as the selective zone of the CoV, positive  frequency and intensity of different normal modes of these structures.The theoretical calculations were done at various levels of theory in water simulated medium to gain the more accurate equilibrium geometrical results, and infrared spectral data for each of the complex proposed drugs of N-terminal or O-terminal auto-cleavage substrate were individually determined to elucidate the structural flexibility and substrate binding of six inhibitors including jointed to TMH, inh[1-6]-TMH. A comparison of these structures with two configurations provides new insights for the design of substrate-based inhibitors targeting CoV. This indicates a feasible model for designing wide-spectrum inhibitors against CoV-associated diseases.The structure-based optimization of these structures has yielded two more efficacious lead compounds, N and O atoms through forming the hydrogen bonding (hydrogen-bonding) with potent inhibition against CoV (Tyr160-Met161-His162) because of water polar medium which has been abbreviated as TMH in this paper.